2017
DOI: 10.1007/s12178-017-9392-9
|View full text |Cite
|
Sign up to set email alerts
|

Tarsal navicular stress fractures

Abstract: Purpose of review Navicular stress fractures are common in athletes and management is debated. This article will review the evaluation and management of navicular stress fractures. Recent findings Various operative and non-operative adjunctive treatment modalities are reviewed including the relevance of vitamin D levels, use of shock wave therapy and bone marrow aspirate concentrate (BMAC), and administration of teriparatide. Surgical treatment may be associated with earlier return to sports. Summary The autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Especially runners who have already had a stress fracture are at high risk of low bone density [ 179 ]. For certain fractures, the preventive use of 25(OH)D is considered [ 180 ]. Up to now it has not been proven that the increased intake of calcium and 25(OH)D is useful for the prevention of stress fractures [ 11 ].…”
Section: 25(oh)d Supplementation As a Preventive Measurementioning
confidence: 99%
“…Especially runners who have already had a stress fracture are at high risk of low bone density [ 179 ]. For certain fractures, the preventive use of 25(OH)D is considered [ 180 ]. Up to now it has not been proven that the increased intake of calcium and 25(OH)D is useful for the prevention of stress fractures [ 11 ].…”
Section: 25(oh)d Supplementation As a Preventive Measurementioning
confidence: 99%
“…Surgical intervention is typically reserved for failure of conservative management, or among elite athletes such as NBA players, particularly with navicular stress fractures. 26 Navicular stress fractures account for 25% of all stress fractures and have a predilection for young, male athletes. 26 Studies have shown that navicular stress fractures were slower to heal, had higher nonunion rates, and resulted in a slower return to activity when managed conservatively.…”
Section: Ankle Fracturementioning
confidence: 99%
“…This is accomplished using a 3.5-to 4.0mm partially or fully threaded cortical lag screw placed percutaneously from medial to lateral. 68,69 Bone marrow aspirate concentrate obtained from the calcaneus is infused at the fracture site to augment healing, particularly if fracture margins are sclerotic. 66 At 10 weeks, CT is usually performed to evaluate healing with the goal of 100% union.…”
Section: Navicularmentioning
confidence: 99%